Analysis Of Factors Influencing Accounting Prudence (Empirical Study On State-Owned Enterprises Listed On The Indonesia Stock Exchange For The Period 2018-2022) - Haniifatuz Zahira Yanadewi; Sugiyarti Fatma Laela (Green Publisher Indonesia, 2024)
This research is to determine the effect of managerial ownership, growth opportunities, financial pressure on prudent accounting with firm size and leverage as additional variables in state-owned companies listed on the Indonesia Stock Exchange (BEI). The research period used is 5 years, namely the 2018-2022 period. The sampling technique in this research is purposive sampling with a selected sample of 18 state-owned companies. The analytical method used to test the hypothesis is panel data regression analysis using Eviews 12. The research results show that managerial ownership, growth opportunities and financial distress have an effect on accounting prudence, while company size and leverage have no effect on accounting prudence. The implication of this research is that company management must be careful in dealing with permits in the future. At this time, they must apply accounting prudence to reduce the risks facing the company.